PERANCANGAN DIGITAL MARKETING SEBAGAI STRATEGI PENGEMBANGAN USAHA SONGKET CEK ONAH PALEMBANG - Purwati, Purwati; Sayuti, Jalaludin; Melati, Nadhira Tasya (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Cek Onah songket business is one of the Palembang songket weaving craftsmen. So far, the products have only been marketed through word of mouth marketing and participating in exhibition activities as a promotional medium, so that the market share has not reached the expected target, and it is necessary to do online marketing as a promotional medium in order to introduce Cek Onah's songket products to the wider community. Instagram is a platform that can be used as a business development through digital marketing. This service aims to design digital marketing through Instagram and publish the results of Instagram content design as a promotional media for Cek Onah's songket business owned by Mrs.Hj.Cek Onah. The target achieved is to produce online promotional media in the form of Instagram post content such as feeds, video reels, and instagram stories to develop and reach a wider business market and can use it as an effort to increase digital marketing of songket woven fabric products so that sales turnover increases and maximum profits are achieved.